Fires and rates of change in the temperate rainforests of northwestern Patagonia since-18 ka - Moreno, Patricio; Mendez, Cesar; Henriquez, Carla A.; Fercovic, Emilia; Videla, Javiera; Reyes, Omar; Villacis, Leonardo A.; Villa Martinez, Rodrigo Patricio; Alloway, Brent (My University, 2023)
We examine the temporal and spatial structure of wildfires and rates of vegetation change in the Pacific sector of northwestern Patagonia (40 degrees-44 degrees S) over the last-18,000 years. Macroscopic Charcoal Accu-mulation Rates (CHAR), a proxy of past local fires, shows a geographic variation that mirrors the modern north-to-south and low-to-high elevation increase in annual precipitation and decrease in precipitation seasonality, and the frequency of explosive volcanic events. Variability in past fires is evident at multiple timescales, with a significant multi-millennial low between-18-13.1 ka, an abrupt rise between-13.1 -12.5 ka, and heightened fire activity between-11.4-8.2 ka with significant high values between-10 -9.4 ka. A subsequent decline led to the lowest Holocene values between-6-5.4 ka, which rose and led to significant high values between-3.1 ka and the present. Andean and Western Upwind Environments share a multi-millennial structure of fire activity since-18 ka, overprinted by millennial and centennial -scale divergences. These differences underscore the role of explosive volcanism as a trigger or modulator of fire activity in the vicinity of Andean eruptive centers. We posit that fire activity in Western Upwind Environments was driven primarily by hydroclimate variations, namely changes in the intensity of the Southern Westerly Winds. Compilations of CHAR and the Rates of Change (ROC) parameter, a measure of the magnitude and rapidity of changes in the pollen records, covary during the onset of the interglacial fire regime at-13.1 ka and the last-4000 years, suggesting that fires catalyzed vegetation changes during specific intervals since the last glaciation. Highly mobile human occupations deployed along the coasts started at-6.2 ka, increased in pulses, and spread widely during the last two millennia. Covariation with CHAR and ROC since-4 ka suggests that hunter-gatherer -fishers contributed to enhanced fire activity and abrupt vegetation changes at regional scale. The ubiquitous fire maximum over the last four cen-turies relates to widespread settlement and associated large-scale land clearance conducted by Euro-pean/Chilean settlers.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: macroscopic charcoal accumulation rates; rates of vegetation change; temperate rainforests; northwestern patagonia; explosive volcanism; human occupations; southern westerly winds; chilean; european settlers